A comprehensive review on heat accounting and cost allocation in residential buildings in EU - Canale, L.; Dell'Isola, M.; Ficco, G.; Cholewa, T.; Siggelsten, S.; Balen, I. (Energy and buildings, 2019)
•In Europe individual metering in residential buildings is mandatory.•Over 130 publications are critically analyzed and reviewed highlighting different EU strategies.•Regulation and technologies for heat accounting and their potential are discussed.•Gap in terms of technical standards and consumer protection is highlighted.•Suggestions to improve transparency and reliability of allocation rules are provided. Since 2002, the European Union (EU) has promoted individual metering of energy consumption as an effective tool to improve energy efficiency in buildings. In 2012, the Energy Efficiency Directive has set mandatory the individual heat accounting in buildings when centralized heating/cooling systems are present, when technically feasible and cost efficient. As a consequence, EU Member States adopted different allocation rules mainly due to differences in building stocks and climatic conditions. This measure has led to a series of technical, legal and consumer protection issues which still need to be solved. In this paper, more than 130 publications have been analysed and critically reviewed, highlighting the different approaches adopted in EU Member States concerning heat accounting and the related issues. To this aim, the authors focussed the following subjects: (i) the allocation rules adopted by EU Member States, (ii) the heat metering and sub-metering technologies, (iii) the cost-benefit analysis of individual heat metering and accounting systems. This review is useful for researchers since the existing regulation and technologies for heat accounting and their related potential are discussed together with the analysis of the existing gap in terms of technical standard and consumer protection. Finally, the analysis provides policy makers with several suggestions to improve transparency and reliability of allocation rules.